Embedded ties and the acquisition of competitive capabilities - McEvily, Bill; Marcus, Alfred (Strategic Management Journal, 2005)
Abstract We build on previous research that explores the external acquisition of competitive capabilities through the embedded ties that firms form in networks and alliances. While information sharing and trust have been theorized to be key features of the interorganizational ties that facilitate the acquisition of competitive capabilities, we argue that these mechanisms provide an incomplete explanation because they do not fully address the partially tacit nature of the knowledge that underlies competitive capabilities. Joint problem‐solving arrangements play a prominent role in capability acquisition by promoting the transfer of complex and difficult‐to‐codify knowledge. Drawing on a set of case studies and a survey of 234 job shop manufacturers we find support for the role of joint problem solving with suppliers in facilitating the acquisition of competitive capabilities. Copyright © 2005 John Wiley & Sons, Ltd.